(untitled) (African Journal of Biomedical Research, 2020)
Menstruation and menstrual hygiene knowledge is fundamental to the health and well-being of adolescent females, however little attention is paid to the acquisition of the right knowledge about this important aspect of adolescent reproductive health in developing counties, Nigeria inclusive. The study was aimed at determining menstruation and menstrual hygiene knowledge among secondary school students as a basis for planning an appropriate health promotion intervention. A cross-sectional study conducted in selected urban and rural secondary schools in Cross River State, Nigeria. Using a semi-structured questionnaire, 1,006 adolescent female students from junior secondary to senior secondary in eight schools were surveyed. The research protocol was approved by the Ethical Review Board of the Cross-River State, Ministry of Health. Of the 1,006 respondents, 600(59.6%) were urban-based while 406 (40.4%) were rural-based. Most 556 (55.3%) were from public schools while 450(44.7%) were from private schools. Mean age was 14.2±2.71 while age at menarche was 10.95±4.10. Age at menarche in urban schools was 11.1±0.157 while that of rural schools was 10.71±0.239. On knowledge, 230(56.7%) rural-based adolescent female students had a significantly poor knowledge of menstruation and menstrual hygiene practices compared with their urban-based counterparts 253 (42.2%). Majority 435(72.5%) in urban and 327(80.5%) in rural schools obtained information about menstruation from their mothers. Similarly, 407(67.8%) in urban schools and 318 (78.3%) from rural schools were informed about menstrual hygiene by their mothers. There is an urban-rural gap in knowledge of menstruation and menstrual hygiene. Parental role in menstrual hygiene education is critical.